"We live in the moment"—Experiences of people with Intellectual Disabilities and Clinicians of Computer‐Assisted Mindfulness and Relaxation. (21st May 2021) - Clyne, Colette; Jackman, Catherine; Tully, Michael; Coyle, David; O'Reilly, Gary
Accessible Summary: Sometimes people find it hard to notice what is going on in their mind, body and feelings. Mindfulness can help us with this. Some studies show that mindfulness might help people with intellectual disabilities. We asked people to play a mindfulness computer game to see whether it helped them to notice their mind, bodies and feelings more easily. People who work with people with intellectual disabilities helped to play the game too. We asked people what they thought about the game. People seem to enjoy playing the game and said it helped them be more mindful. We think that learning mindfulness in a computer game might be helpful for people with intellectual disabilities. Abstract: Background: This paper evaluates the user experience of a newly developed mindfulness and relaxation game designed to teach mindfulness skills to people with intellectual disabilities. Computer‐assisted mindfulness programs have gained considerable attention among researchers in both adult and child populations. However, less is known about the experiences of people with intellectual disabilities who engage in computerised mindfulness programs. The present study aimed to explore the experiences of adults with intellectual disabilities and clinicians in using a computerised mindfulness and relaxation game. Method: Twelve adults (with a mild or moderate intellectual disability) and sixteen clinicians were individually interviewed. Thematic analysis was used to analyse and generate themes within the data. Findings: Three main themes with a number of subthemes were generated for people with intellectual disabilities including the following: (1) The Process of Mindful Island; (2) Fostering Relationships Through the Computer; and (3) The Impact of the Game. Three themes from clinician interviews were also generated including the following: (1) A Good Concept but More to Do; (2) Uncertainties Around Players' Understanding of Mindfulness; and (3) The Computer as a Tool to Build Relationships. The findings indicated that participants found the game an enjoyable experience and saw a number of benefits to engaging in it including perceived improved confidence and perceived reduction of worries. Conclusions: Mindfulness can be adapted to computer‐assisted technology for use among people with intellectual disabilities and may foster a number of benefits.